HUBUNGAN LINGKUNGAN FISIK DAN SANITASI DENGAN ANGKA KUMAN LANTAI RUANG PERSALINAN BIDAN PRAKTIK SWASTA WILAYAH PUSKESMAS LOA DURI - Nanik Sri Wulandari (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2018)
Health development in Indonesia is still affected by the health status of women pregnancy, labor, puerperal period, and perinatal period, indicated by the high rate of maternal mortality and perinatal mortality. One effort that has been made is providing quality midwifery service. This research aimed to find out the correlation between physical environment and sanitation and total floor germs in maternity rooms of private midwife practice in the area of Puskesmas Loa Duri. This research used Cross Sectional Study design. The object of this research was four maternity rooms of private midwife practice in the area of Puskesmas Loa Duri with inclusion criteria as follows: active, having practice license, the rooms were separated from the living rooms,  accepting and serving the patients for 24 hours and willing to participate in this research.  The data were analyzed by using univariate and bivariate analysis with Rank Spearman Statistical test (? = 0.05).The research findings showed that there were 75% of the maternity rooms with total floor germs, temperatures, lighting and sanitation which did not meet the requirements and only 25% of the rooms which met the requirement based on the Decree of Health Ministry of Republic of Indonesia Number 1204/Menkes/SK/X/2004.  There were 4 research variables which did not correlate with total floor germs, namely: temperature (p = 0.684), humidity (p = 0.600), lighting (p = 0,200) and room sanitation (p =0.684). However, coefficient of correlation (r) showed a negative correlation for the variables  of temperature, lighting and sanitation (-0.316, -0.800 and -0.316), meaning that the higher the value of those variables the smaller the total floor germs would be, while humidity had a positive correlation (0.400), meaning that the higher the humidity, the higher the total floor germs would be. Lighting had the strongest correlation with the total floor germs in the maternity rooms of private midwife practice in the area of Puskesmas Loa Duri.Keywords: Total floor germs, physical environment, sanitation, private midwife practice